Cis-Nerolidol Inhibits MAP Kinase and NF-κB Signaling Pathways and Prevents Epithelial Tight Junction Dysfunction in Colon Inflammation: In Vivo and In Vitro Studies - Raj, Vishnu; Venkataraman, Balaji; Ojha, Shreesh K.; Almarzooqi, Saeeda; Subramanian, Veedamali S.; Al-Ramadi, Basel K.; Adrian, Thomas E.; Subramanya, Sandeep B. (Molecules (Basel, Switzerland), 2023)
Inflammation of the GI tract leads to compromised epithelial barrier integrity, which increases intestine permeability. A compromised intestinal barrier is a critical event that leads to microbe entry and promotes inflammatory responses. Inflammatory bowel diseases that comprise Crohn’s disease (CD) and ulcerative colitis (UC) show an increase in intestinal permeability. Nerolidol (NED), a naturally occurring sesquiterpene alcohol, has potent anti-inflammatory properties in preclinical models of colon inflammation. In this study, we investigated the effect of NED on MAPKs, NF-κB signaling pathways, and intestine epithelial tight junction physiology using in vivo and in vitro models. The effect of NED on proinflammatory cytokine release and MAPK and NF-κB signaling pathways were evaluated using lipopolysaccharides (LPS)-stimulated RAW 264.7 macrophages. Subsequently, the role of NED on MAPKs, NF-κB signaling, and the intestine tight junction integrity were assessed using DSS-induced colitis and LPS-stimulated Caco-2 cell culture models. Our result indicates that NED pre-treatment significantly inhibited proinflammatory cytokine release, expression of proteins involved in MAP kinase, and NF-κB signaling pathways in LPS-stimulated RAW macrophages and DSS-induced colitis. Furthermore, NED treatment significantly decreased FITC-dextran permeability in DSS-induced colitis. NED treatment enhanced tight junction protein expression (claudin-1, 3, 7, and occludin). Time-dependent increases in transepithelial electrical resistance (TEER) measurements reflect the formation of healthy tight junctions in the Caco-2 monolayer. LPS-stimulated Caco-2 showed a significant decrease in TEER. However, NED pre-treatment significantly prevented the fall in TEER measurements, indicating its protective role. In conclusion, NED significantly decreased MAPK and NF-κB signaling pathways and decreased tight junction permeability by enhancing epithelial tight junction protein expression.